Between the market and the developmental state – the place and limits of pro-poor ENGO led "waste-preneurship" in South Africa. Issue 12 (2nd December 2022) - Thakur, Shaheen Sewparsadh; Nel, Adrian
ABSTRACT: Southern Waste geographies have focused on informal waste-picking and the emergence of neoliberal waste regimes as responses to inadequate Household Solid Waste Management (HWSM) – exploring cost-benefit relationships, labour, and market dynamics, respectively. Less understood regarding reconfigurations of waste governance is the role and performance of Environmental Non-Governmental Organisations (ENGOs) that have attempted to improve HSWM and recycling practices through Community-Based Recycling Interventions (CBRIs). Exploring the case of Wildlands Conservation Trust (WCT) " wastepreneur " initiative in rural and peri-urban communities in Kwazulu-Natal, South Africa, this study sought to critically assess the sustainability and labour dynamics of the intervention, highlighting its response to changing conditions. The project had initial successes in both facilitating and compensating pro-poor peri-urban waste-picking, generated high expectations and positively impacted recycling practices and perceptions in the process. After a point, however, the initiative experienced financial and institutional challenges which precipitated a restructuring of the initiative in line with prevailing recycling market dynamics – of which it had been naïve – and changing government labour funding; fostering a significant downscaling and disappointment on the part of participants. The findings highlight the limitations of CBRIs in hybrid governance contexts and with underdeveloped recycling markets, and the need for analysis that moves beyond critiques of neoliberalism to consider the ongoing role of the developmental state in local urban service provision.